AI trust and protean career among university students: the mediating role of intrinsic motivation and the moderating role of job insecurity - Jiang, Juan; Chen, Jiachun (Frontiers in Psychology, 2026)
Amid the growing integration of artificial intelligence (AI) into the labor market, university students have to develop career orientation that aligns with the constant state of technological change. Drawing on self-determination theory and conservation of resources theory, we examine how AI trust influences university students' protean careers, while also considering the roles of intrinsic motivation and job insecurity. A survey of 576 undergraduates in Guangdong Province was conducted and analyzed using structural equation modeling. There are four key findings revealed by the results. First, AI trust significantly and positively influences university students' intrinsic motivation. Second, intrinsic motivation is positively associated with protean career. Third, intrinsic motivation mediates the relationship between AI trust and protean career. Fourth, job insecurity simultaneously intensifies the effect of AI trust on intrinsic motivation and enlarges the subsequent mediated path through which AI trust, via intrinsic motivation, translates into stronger protean career orientation. These findings shed new light on the psychological micro-behavior mechanisms by which technological beliefs influence career attitudes, and offer pragmatically useful implications for AI-related education programs, university career counseling, corporate personnel management, and the self-development of students.